PENGARUH UKURAN PERUSAHAAN DAN GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN CONSUMER NON-CYCLICALS YANG TERDAFTAR DI BURSA EFEK INDONESIA: PENGARUH UKURAN PERUSAHAAN DAN TATA KELOLA PERUSAHAAN YANG BAIK TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENSI PADA PERUSAHAAN KONSUMEN NON-SIKLIKAL YANG TERDAFTAR DI BURSA EFEK INDONESIA - Nopita Sari (Sumatera Scientist, 2025)
This study aims to determine how much influence company size, good corporate governance (GCG), has on company value with financial performance as an intervening variable. The population of this study is non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX) in the period 2019-2023. The sampling technique used is purposive sampling with criteria that have been determined by the researcher and obtained 41 out of 129 non-cyclical consumer sector companies. The analysis method used is multiple linear regression analysis and path analysis using SPSS 21 software.The results of the study obtained based on the partial test (t-test) obtained company size has a negative and significant effect on financial performance with a probability value of 0.005. Good corporate governance (GCG) does not have a significant effect on financial performance with a probability value of 0.170. Company size does not have a significant effect on company value with a probability value of 0.869. Good corporate governance (GCG) has a positive and significant effect on company value with a probability value of 0.042. Company size has a positive and significant effect on company value with a probability value of 0.000. Company size has a negative and significant effect on company value through financial performance as an intervening variable, where the direct effect value is smaller than the indirect effect -0.010 < 0.0512. Good corporate governance (GCG) does not have a significant effect on company value through financial performance as an intervening variable, where the direct effect value is greater than the indirect effect value 0.0652 > 0.121.